2005
DOI: 10.1152/ajpendo.00115.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin regulates mitochondrial-lipid metabolism gene expression and tissue fat distribution in liver and skeletal muscle

Abstract: . Ghrelin regulates mitochondrial-lipid metabolism gene expression and tissue fat distribution in liver and skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
175
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 59 publications
20
175
3
3
Order By: Relevance
“…It is also probable that in the group of the youngest foals investigated here, the increase in plasma leptin concentration induced the rise in plasma ghrelin concentration. Ghrelin might also integrate the energy balance by the decrease of lipid oxidation in the liver, and favors fat utilization in muscles (Barazzoni et al, 2005). The appearance of a low level of this peptide after exercise promotes the utilization of fat in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also probable that in the group of the youngest foals investigated here, the increase in plasma leptin concentration induced the rise in plasma ghrelin concentration. Ghrelin might also integrate the energy balance by the decrease of lipid oxidation in the liver, and favors fat utilization in muscles (Barazzoni et al, 2005). The appearance of a low level of this peptide after exercise promotes the utilization of fat in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of low-caloric diets and chronic exercise, ghrelin levels were increased; and in states of obesity or after glucose challenge, the concentrations of this peptide were reduced (Meier and Gressner, 2004;. Ghrelin stimulates the release of the growth hormone from the pituitary gland and increases appetite, food intake, body weight (BW), energy balance and especially fat tissue by decreasing fat oxidation in the liver (Matyjek et al, 2004;Barazzoni et al, 2005). The value of this peptide decreases over the period of childhood and puberty (Broglio et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin has previously been shown to enhance UCP2 mRNA expression in the pancreas (Sun et al 2006), liver (Barazzoni et al 2005), and white adipose tissue (Tsubone et al 2005). In the Andrews' study, ghrelin was shown to increase hypothalamic UCP2 mRNA expression (Andrews et al 2008).…”
Section: Ghrelin Acts Via Ucp2mentioning
confidence: 92%
“…In contrast, ghrelin inhibits lipid oxidation, decreasing activity and gene expression of the liver isoform of carnitine palmitoyltransferase 1 (CPT1A) (Barazzoni et al 2005;Sangiao-Alvarellos et al 2009;Theander-Carrillo et al 2006). …”
Section: Page 5 Of 37mentioning
confidence: 99%
“…In the hypothalamus, central and peripheral ghrelin treatments enhance protein levels of AMPK and this activation and alterations on lipid metabolism mediate the Page 17 of 37 A c c e p t e d M a n u s c r i p t 17 orexigenic effects of ghrelin (Andersson et al 2004;Kohno et al 2008;Kola et al 2005Kola et al , 2008Lopez et al 2008). In fed animals peripheral chronic and acute ghrelin treatments provoked AMPK activation in the heart, while in liver and adipose tissue it was inhibited and no effect was detected on skeletal muscle (Barazzoni et al 2005;Kola et al 2005). In this work we showed that ghrelin neutralization caused lower AMPK total protein levels after 48 hours of refeeding compared with their controls, just like during 48 hours of fasting.…”
mentioning
confidence: 99%